Investigation of p-y Behaviors of a Cyclic Laterally Loaded Pile in Saturated Silty Sand - Sung-Ha Baek; Joonyoung Kim (Advances in Civil Engineering)
This study aimed to evaluate the p-y behavior of pile foundations installed in saturated silty sand subject to cyclic lateral loading. Model piles were installed in saturated silty sand with three relative densities (40%, 70%, 90%), and lateral loads of three magnitudes were repeatedly applied. The model test results revealed that as the cyclic lateral loading was applied to the piles, the soil around the piles became densified in the loose soil (relative density of 40%), and the stiffness of the p-y curve increased. In contrast, in dense soil (relative density of 70% and 90%), the stiffness of the p-y curve decreased as the soil around the piles was disturbed. Special attention was devoted to the development of static and cyclic p-y curves for assessing the lateral behavior of offshore pile foundations installed in saturated silty sand. A comparison between the p-y curves derived in this study and the existing p-y curves for silica sand revealed that the existing p-y curves were more likely to overestimate the lateral load capacity of a pile installed in silty sand.